ANALISIS PERBANDINGAN PENGHEMATAN KONSUMSI ENERGI LISTRIK DAN PERENCANAAN PEMBANGKIT LISTRIK TENAGA HYBRYD MENUJU LOW ENERGY BUILDING PADA HOTEL MERCURE PONTIANAK DAN HOTEL IBIS STYLES BANDARA SOEKARNO HATTA JAKARTA - Teddy Gama Silalahi; Stepanus Stepanus; Bambang Widodo (Prodi Teknik Elektro FT UKI, 2019)
In the current era of technological and information advancements, the growth of industry and business is becoming faster and faster. But this also encourages higher energy use and makes energy use a major contribution to operational costs that must be spent. This study aims to conduct a comparative analysis of Energy Consumption Intensity (IKE) at the Mercure Pontianak Hotel and the Ibis Styles Hotel SoekarnoHatta Airport Jakarta. The method used in this study is the Survey and Literature Study methods. Primary data is obtained from the 2018 Electricity Bill. The data is then used to calculate the Energy Consumption Intensity and then a simulation of energy savings using solar solar with Homer software simulation. The results showed that the IKE in the Mercure Pontianak Hotel building is bigger than the Ibis Styles Hotel SoekarnoHatta Airport which is 323,390 kWh / m2 / year meaning the energy usage in the Mercure Pontianak Hotel building is greater than the Ibis Styles Hotel SoekarnoHatta Airport Jakarta building with a difference of 79,389 kWh / year with a building age difference of +/- 5 years older Mercure Pontianak Hotel while the building area and number of rooms are almost the same. The simulation results of using solar cells obtained energy production of 221,866 kWh per year at a cost of Rp. 972 / kWh, meaning energy savings of 6-8% a year.